The relationship between actual and self-perceived physical fitness in adolescence - Bezjak, Robert (Array, 2021)
The purpose of this study was to assess the relationship between physical self-concept and actual indicators of physical fitness in early and mid-adolescence. Physical self-concept plays a significant role in adolescence, as this phase of life is characterised by many physical, mental, and emotional changes. A total of 427 Slovenian boys and girls from two age groups (early and middle adolescence) were studied. Physical self-concept was assessed with the Slovenian version of Physical Self-Description Questionnaire, while the Sports-educational Chart was used to measure physical fitness. The results showed that the older group scored better on all measures of physical fitness, except for general endurance. In terms of age-related differences in physical self-concept, older adolescents showed poorer physical perceptions of their strength and flexibility and higher global self-esteem compared to their younger peers. Correlation analysis showed that physical self-concept and actual indicators of physical fitness were related, despite incomplete overlap between psychological dimensions and objective measures. The obtained results can be transferred to physical education, as the development of a positive physical self-concept is one of the most important educational goals.